Patterns of Avoidance Behavior in Response to Fear of Victimization in the Mexican Context: A Latent Class Analysis - Borja, Sharon (Journal of interpersonal violence, 2024)
Fear of victimization (FOV) is a powerful determinant of behavior and prompts behavioral responses such as avoidance, associated with a decline in health-promoting activities and quality of life. Avoidance behaviors, which include constraining activities to perceived safe areas and avoiding areas regarded as unsafe, are of particular interest due to their high prevalence as a coping response to FOV and their link to adverse physical and mental health. Most research on FOV-related avoidance treats it as a single construct and have yet to elucidate the potential heterogeneity within this set of behaviors. We argue that such approach could mask potential heterogeneity among people who respond to FOV through avoidance and how they adapt to manage perceived risk. Our analysis extends the foundational knowledge regarding FOV-related avoidance using a person-centered approach. We attempted to capture distinct profiles across avoidance behaviors and how they are shaped by physical and social vulnerabilities. Data from the 2021 Mexico’s National Survey of Victimization and Perception of Security Survey (n = 83,696) was analyzed using Latent Class Analysis focusing on 15 avoidance behaviors (e.g., stopped using public transportation). We conducted multinomial logistic regression to test whether age, gender, education, and neighborhood deprivation significantly predicted class membership. Findings revealed three classes: avoidant (most behavioral adjustments across the board), cautious (only adapted some behaviors), and protective (least behavioral adjustments, but more concerned about minors in their households). The results supported the hypothesized associations between age, gender, education, and neighborhood deprivation with group membership, but the significance differed by group. This research underscores the role of environmental context in shaping individual perceptions of safety and avoidance behavior. Finally, contrary to the approach of treating avoidance behavior as a single category, these findings present a more complex picture as distinct and meaningful patterns emerged across the three groups.